Family values reconsidered: a response. Issue 3 (4th May 2018) - Brighouse, Harry; Swift, Adam
Abstract: It is wonderful to receive so much careful attention. But it's also frustrating. Each paper poses important questions, and between them they cover a wide range of issues. It is challenging, on such big topics, and in so few words, simultaneously to set the record straight, to identify the various objections posed by our critics, and to respond to them in a way likely to advance our collective understanding of the issues. Still, here goes.